The Effect of Mindfulness- Based Cognitive Therapy and Cognitive Behavior Therapy on Cognitive Emotion Regulation in Women with Vaginismus - Zahra Omidvar; Mohammad Hossien Bayazi; Farhad Faridhosseini (Mashhad University of Medical Sciences, 2021)
Introduction: Vaginismus is one of the sexual dysfunctions in women. Emotional regulation refers to the actions which are used to change or modify an emotional state. This study was performed with aim to compare the effect of mindfulness- based cognitive therapy and cognitive behavior therapy on cognitive emotion regulation in women with vaginismus.Methods: This quasi-experimental study was performed in 2018 on 45 women with vaginismus referred to Rahyab Psychology Counseling Clinic in Mashhad. The subjects were randomly divided into three groups of 15 people including two intervention groups and one control group. The women of one intervention group received cognitive-behavioral techniques and the other group received mindfulness-based cognitive therapy; the control group did not receive any intervention. The research tools were demographic questionnaire and cognitive emotion regulation questionnaire. Data were analyzed by SPSS software (version 20) and multivariate and univariate analysis of covariance and Bonferroni post hoc test. P<0.05 was considered statistically significant.Results: Both mindfulness-based cognitive therapy and cognitive-behavioral therapy methods were effective on improving the cognitive emotion regulation dimensions of women with vaginismus compared to the control group (P = 0.0001). Considering the comparison of the differences between the means of the two intervention groups with the control group, mindfulness-based cognitive therapy has a greater effect on the dimensions of cognitive emotion regulation than cognitive-behavioral therapy (P <0.01).Conclusion: Although both mindfulness-based cognitive therapy and cognitive-behavioral therapy have were effective on the cognitive emotion regulation in women with vaginismus, but the effect of mindfulness-based cognitive therapy is greater than cognitive-behavioral therapy.